1999
DOI: 10.1037/h0087087
|View full text |Cite
|
Sign up to set email alerts
|

La conception de la santé chez des garçons de 14 à 16 ans de milieu défavorisé.

Abstract: ResumeDans le but de decrire leur conception de la sante, des entrevues individuelles ont ete conduites aupres de 700 garcons de 14 a 16 ans de milieu defavorise. Une analyse de contenu classique a ete realisee sur les verbalisations des jeunes et des taux d'accords interjuges ont ete calcules. La capacite d'assumer ses activites de facpn optimale, les habitudes de vie saines et, dans une moindre mesure, la sante mentale caracterisent leur conception de la sante. Les adolescents accentuent 1'importance dans le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the whole, the students' perceptions were quite similar to those of the adults who were questioned, and to those of the society as a whole. Other studies have shown that adolescents' perception or their preoccupations with health issues reflect what adults instill into them (Jutras, Tremblay and Morin, 1999); and, in this sense they reflect th'e customs of a society or its tradition (Duong Dinh Cong, Vo Thi Xuan Hanh, Ho Th Huonngn and Deschamps, 2001). These findings lead us on one hand to conclude that training of health professionals must take adolescents' perceptions about health into account and, on the other hand, that we must be more vigilant that boys have access to health care and that means to interpret their psychological suffering be available.…”
Section: Advancing Knowledgementioning
confidence: 99%
“…On the whole, the students' perceptions were quite similar to those of the adults who were questioned, and to those of the society as a whole. Other studies have shown that adolescents' perception or their preoccupations with health issues reflect what adults instill into them (Jutras, Tremblay and Morin, 1999); and, in this sense they reflect th'e customs of a society or its tradition (Duong Dinh Cong, Vo Thi Xuan Hanh, Ho Th Huonngn and Deschamps, 2001). These findings lead us on one hand to conclude that training of health professionals must take adolescents' perceptions about health into account and, on the other hand, that we must be more vigilant that boys have access to health care and that means to interpret their psychological suffering be available.…”
Section: Advancing Knowledgementioning
confidence: 99%
“…Although the original focus of the MLES was on the development of antisocial behavior, investigators became interested in the development of many other dimensions of human development, some closely related to antisocial behavior, such as hyperactivity (e.g., Pulkkinen & Tremblay, 1992;Soussignan et al), anxiety (e.g., Dobkin, Treiber, & Tremblay, 2000;, substance use and abuse (e.g., Carbonneau et al, 1998;Dobkin, Tremblay, & Sacchitelle, 1997;Mâsse & Tremblay, 1997), gambling(e.g., Vitaro,Arseneault, & Tremblay, 1997;Vitaro, Arseneault, & Tremblay, 1999), school performance (e.g., Haapasalo, Tremblay, Boulerice, & Vitaro, 2000;Pagani, Tremblay, Vitaro, Boulerice, & McDuff, 2001), accidents (e.g., Junger & Tremblay, 1999;Tremblay, Boulerice, Junger, & Arseneault, 1995), heart rate variability (e.g., Kindlon et al, 1995;Mezzacappa et al, 1997), pubertal maturation, sexual intercourse and testosterone (e.g., Malo & Tremblay, 1997;Schaal, Tremblay, Soussignan, & Susman, 1996;Tremblay et al, 1997;Tremblay et al, 1998), perinatal complications (Arseneault, Tremblay, Boulerice, & Saucier, 2002;Pagani, Tremblay, Vitaro, & Parent, 1998), physical anomalies (Arseneault, Tremblay, Boulerice, Séguin, & Saucier, 2000), poverty (Pagani, Boulerice, Vitaro, & Tremblay, 1999), and others less closely related, such as nutrition (e.g., , olfaction (Schaal, Rouby, Marlier, Soussignan, Kontar, & Tremblay, 1998), pain sensitivity (Ditto, Séguin, Boulerice, Pihl, & Tremblay, 1998), and physical health (Dobkin, Tremblay, & Treiber, 1998;Jutras, Tremblay, & Morin, 1999).…”
Section: Aims and Design Of The Studymentioning
confidence: 99%